Administrative boundary of Kiteto, Kilindi, Chalinze and Mvomero districts - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing the administrative boundaries of Chalinze, Kiteto, Kilindi and Mvomero districts, in Coastal (Pwani), Tanga, Morogoro and Manyara regions, Tanzania.